2011
DOI: 10.1051/0004-6361/201117476
|View full text |Cite
|
Sign up to set email alerts
|

GOODS-Herschel: the impact of galaxy-galaxy interactions on the far-infrared properties of galaxies

Abstract: Aims. We study the impact of galaxy-galaxy interactions on the far-infrared properties of galaxies and its evolution at 0 < z < 1.2. Methods. Using the high-z galaxies in the fields of Great Observatories Origins Deep Survey (GOODS) observed by the Herschel Space Observatory in the framework of the GOODS-Herschel key program and the local IRAS or AKARI-selected galaxies in the field of Sloan Digital Sky Survey Data Release 7, we investigate the dependence of galaxy properties on the morphology of and the dista… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 114 publications
2
33
1
Order By: Relevance
“…In this sense, what is the reason for this enhancement in SFR, considering that this enhancement is not the typical case for spirals in S+E pairs, as shown by Xu et al (2010), and more recently by Cao et al (2016). Indeed, in the case of S+E pairs, Hwang et al (2011) suggest that the X-ray emission associated with an elliptical galaxy could suppress the SFR in its companion spiral, but this seems to not be the case for NGC 2936, probably due to the mass of the elliptical companion, which is not high enough to suppress the star Figure 9. Snapshot of total mass (star+gas) for the simulated system.…”
Section: Arp 142: a Peculiar S+e Pair Of Galaxiesmentioning
confidence: 94%
“…In this sense, what is the reason for this enhancement in SFR, considering that this enhancement is not the typical case for spirals in S+E pairs, as shown by Xu et al (2010), and more recently by Cao et al (2016). Indeed, in the case of S+E pairs, Hwang et al (2011) suggest that the X-ray emission associated with an elliptical galaxy could suppress the SFR in its companion spiral, but this seems to not be the case for NGC 2936, probably due to the mass of the elliptical companion, which is not high enough to suppress the star Figure 9. Snapshot of total mass (star+gas) for the simulated system.…”
Section: Arp 142: a Peculiar S+e Pair Of Galaxiesmentioning
confidence: 94%
“…Xu et al (2012) also found no significant sSFR enhancement in massive S+E pairs at any redshift. Other authors have shown this absence of SFR enhancements in S+E pairs and low SFR of spirals with early type neighbors (Park et al 2008;Park & Choi 2009;Hwang et al 2011;Moon & Yoon 2015). Park et al (2008) suggest the hot x-ray halo of early type companions interacts hydrodynamically and deprives their paired spirals of cold gas and reduces SFRs.…”
Section: Introductionmentioning
confidence: 94%
“…On the other hand, it was found that galaxy properties such as morphology, luminosity, and star formation rate (SFR) strongly depend on the distance to and the morphology of the nearest neighbor galaxy, which indicates an important role of hydrodynamic interactions with neighbor galaxies (Park et al 2008;Hwang et al , 2011. This dependence was found even when the large-scale background density is fixed, and thus is completely different from the commonly known morphology − local density relation.…”
Section: Introductionmentioning
confidence: 95%